2015
DOI: 10.1080/15332667.2015.1041353
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Value, Reputation, Trust, and Switching Costs as Determinants of Customer Retention

Abstract: In service companies, maintenance and expansion of relational exchanges reinforce customer retention as a differentiator from the competition. In this research we developed and tested a theoretical model considering perceived value, service provider reputation, trust, and switching costs as determinants of customer retention. After that, a survey was done, and analysis of the results was performed using structural equation modeling with a sample of 269 client companies of corporate health plans. The contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 47 publications
(48 reference statements)
4
35
0
4
Order By: Relevance
“…These findings support previous research in customer relationship management which links customer perceived value and customer retention. For instance, Milan et al, (2015) established that clients in the corporate market are more willing to keep relationships with existing suppliers if they are being attended to with elevated value. The findings are also supported by the ideas of Carlos et al,(2006), who suggested that a relationship journey between a bank and its customer where both parties hope to obtain certain advantages and benefits (value) through the working and development of the relationship, the advantages that the service provider obtains from the relationship are linked to the loyalty of the customer.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support previous research in customer relationship management which links customer perceived value and customer retention. For instance, Milan et al, (2015) established that clients in the corporate market are more willing to keep relationships with existing suppliers if they are being attended to with elevated value. The findings are also supported by the ideas of Carlos et al,(2006), who suggested that a relationship journey between a bank and its customer where both parties hope to obtain certain advantages and benefits (value) through the working and development of the relationship, the advantages that the service provider obtains from the relationship are linked to the loyalty of the customer.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the way a business owner's brand makes a customer feel can affect brand equity (Aaker, 1991;Milan, Eberle, & Bebber, 2015). The brand association has substantial value to brand managers.…”
Section: Brand Associationsmentioning
confidence: 99%
“…The implication of this is that perceived value constitutes barriers to the exchange of supplier or service provider. Studies evidence that perceived value has a direct impact on service provider reputation (Milan et al, 2015a;Milan et al, 2015b). This way, the first research hypothesis was formulated: H1: Perceived value positively influences service provider reputation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A service company, that constantly seeks for a good reputation, aggregates psychological value to its services and decreases the risks perceived by the customer in the (re)purchase process (Dowling, 2001) and that may create a narrow connection between the customer and the company (Milan et al, 2015b). This way, a good reputation besides increasing switching costs, helps shaping customers' future behavior in relation to the company (Davies et al, 2010), improving its image in the market (Fombrun, 1996) and empowering customers' loyalty (Dunn & Schweitzer, 2005;Bartikowski & Walsh, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%